2020
DOI: 10.1111/jphp.13252
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel-like factor 2 disturb non-small cell lung cancer energy metabolism by inhibited glutamine consumption

Abstract: Objectives Metabolic reprogramming is well accepted as a hallmark of cancer. This study aimed to explore the role of Kruppel-like factor 2 (KLF2) in aerobic glycolysis and glutamine consumption of energy metabolism in non-small cell lung cancer (NSCLC) cells. Methods Two different NSCLC cells, A549 and NCI-H1299, were used to investigate the role of KLF2 in glycolysis and glutamine consumption by tracer technique and KLF2 transfection. Key findings The results showed that overexpression KLF could inhibit the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…31 In addition, KLF2 re-expression disturbed the proliferation of lung cancer cells by disappearing energy metabolism through glutaminase inhibition. 32 In our study, we also observed an increase of miR-1206 and a decrease of KLF2 in lung cancer tissues and cells. Moreover, miR-1206 promoted cancer cell proliferative, invasive, migratory, angiogenetic abilities, which were reversed by KLF2.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…31 In addition, KLF2 re-expression disturbed the proliferation of lung cancer cells by disappearing energy metabolism through glutaminase inhibition. 32 In our study, we also observed an increase of miR-1206 and a decrease of KLF2 in lung cancer tissues and cells. Moreover, miR-1206 promoted cancer cell proliferative, invasive, migratory, angiogenetic abilities, which were reversed by KLF2.…”
Section: Discussionsupporting
confidence: 73%
“…In lung cancer, KLF2 expression was found to be decreased; restoration of KLF2 inhibited lung cancer cell proliferation 31 . In addition, KLF2 re‐expression disturbed the proliferation of lung cancer cells by disappearing energy metabolism through glutaminase inhibition 32 . In our study, we also observed an increase of miR‐1206 and a decrease of KLF2 in lung cancer tissues and cells.…”
Section: Discussionsupporting
confidence: 70%
“…For instance, DNA-damage inducible transcript 3 ( Ddit3 ) regulates endoplasmic reticulum (ER) stress–induced apoptosis ( 20 ). Krüppel-like factor 2 ( Klf2 ) has been reported to be involved in the inhibition of cell proliferation ( 21 ). In fact, we recently showed that under conditions of constant stimulation, renin cells do not proliferate ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Their transcription factor repertoire suggested the cells sustained cellular stress as indicated by the expression of DNA-damage inducible transcript 3 (Ddit3) known to regulate ER stress-induced apoptosis (20). Also, the cells expressed Krüppel-like Factor 2 (Klf2), which has been reported to be involved in the inhibition of cell proliferation (21), indicating that these cells are not proliferative and they increase their numbers by phenotypic switching and cell transformation. In addition to their unique circuitry of transcription factors, the null cells synthesize a large variety of secreted proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells have a high level of the glutamine consumption to prepare their required energy for the cell proliferation and growth [ 97 , 98 ]. It was shown that KLF2 significantly reduced the NSCLC cell proliferation through the reduced glutamine consumption following the glutamine transaminase down regulation [ 99 ].…”
Section: Introductionmentioning
confidence: 99%